Childhood-Onset Myasthenia Gravis Patients Benefited from Thymectomy in a Long-Term Follow-up Observation - Zhang, Qing; Cao, Yayun; Bi, Zhuajin; Ma, Xue; Yang, Mengge; Gao, Huajie; Gui, Mengcui; Bu, Bitao (European Journal of Pediatric Surgery, 2022)
Introduction The effect of thymectomy on the treatment of childhood-onset myasthenia gravis (CMG) remains debatable. The objective of this study was to evaluate the clinical outcome and relevant prognostic factors of thymectomy for CMG patients.Materials and Methods A total of 32 CMG patients who underwent thymectomy before 18 years of age were included in this retrospective study. Clinical state following thymectomy was assessed by quantified myasthenia gravis (QMG) scores, myasthenia gravis–related activities of daily living (MG-ADL) scores, and Myasthenia Gravis Foundation of America postintervention status. Repeated-measures analysis of variance (ANOVA) examined the changes in postoperative scores during the 5-year follow-up. Univariate logistic regression was applied to identify factors associated with short-term (1-year postoperation) and long-term (5-year postoperation) clinical outcomes.Results Repeated-measures ANOVA showed that QMG scores (F = 6.737, p < 0.001) and MG-ADL scores (F = 7.923, p < 0.001) decreased gradually with time. Preoperative duration (odds ratio [OR] = 0.85, 95% confidence interval [CI]: 0.73–1.00, p = 0.043), gender (OR = 0.19, 95% CI: 0.04–0.94, p = 0.041), and MG subgroup (OR = 13.33, 95% CI: 1.43–123.99, p = 0.023) were predictors for 1-year postoperative prognosis. Shorter disease duration (OR = 0.82, 95% CI: 0.70–0.97, p = 0.018) and generalized CMG (OR = 6.11, 95% CI: 1.06–35.35, p = 0.043) were found to have more favorable long-term results.Conclusion Our results suggest that thymectomy is effective in treating CMG. Thymectomy could be recommended for CMG patients, especially for patients in the early course of GMG.
Keywords: childhood-onset myasthenia gravis; thymectomy; prognosis